(untitled) - Dahm, Kevin D. (Stamford, CT, 2015)
Presenting through a problem-solving inductive learning approach, written in a conversational and approachable manner; The approach taken stresses problem-solving, and draws from "best practice" engineering teaching strategies; the material is helpful to all readers, particularly to global learners who require "big picture" insights, and hands-on learners who struggle with abstractions.
Nhiệt động lực học và truyền nhiệt
Keywords: Hóa kỹ thuật,Chemical engineering